Phonon fingerprints of CsPb2Br5. (17th September 2018) - Hadjiev, V G; Wang, C; Wang, Y; Su, X; Calderon, H A; Robles Hernandez, F; Wang, Z M; Bao, J M
Abstract: CsPb2 Br5 is a stable, water-resistant, material derived from CsPbBr3 perovskite and featuring two-dimensional Pb–Br framework separated by Cs layers. Both compounds can coexist at nanolength scale, which often produces conflicting optical spectroscopy results. We present a complete set of polarized Raman spectra of nonluminescent CsPb2 Br5 single crystals that reveals the symmetry and frequency of nondegenerate Raman active phonons accessible from the basal (0 0 1) plane. The experimental results are in good agreement with density functional perturbation theory simulations, which suggests that the calculated frequencies of yet unobserved double degenerate Raman and infrared phonons are also reliable. Unlike CsPbBr3, the lattice dynamics of CsPb2 Br5 is stable as evidenced by the calculated phonon dispersion. The sharp Raman lines and lack of a dynamic-disorder-induced central peak in the spectra at room temperature indicate that the coupling of Cs anharmonic motion to Br atoms, known to cause the dynamic disorder in CsPbBr3, is absent in CsPb2 Br5 .